2006
DOI: 10.1017/s0033291706007744
|View full text |Cite
|
Sign up to set email alerts
|

Brain reserve and cognitive decline: a non-parametric systematic review

Abstract: This study affirms that the link between behavioural brain reserve and incident dementia is most likely due to fundamentally different cognitive trajectories rather than confound factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
216
0
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(242 citation statements)
references
References 27 publications
5
216
0
15
Order By: Relevance
“…Epidemiological studies have shown lower prevalence or incidence of dementia in elder population with high level of education (see Meng andD"Arcy, 2012 andValenzuela et al, 2006 for a review and meta-analysis). Furthermore, neuropsychological studies have reported better cognitive test performance (Plassman et al, 1995;Wilson et al, 2009) and reduced rate of cognitive decline (Albert et al, 1995;Alvarado et al, 2002;Anstey et al, 2003;Christensen et al, 1997;Evans et al, 1993;Farmer et al, 1995;Lyketsos et al, 1999;White et al, 1994) in elders with higher levels of education.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown lower prevalence or incidence of dementia in elder population with high level of education (see Meng andD"Arcy, 2012 andValenzuela et al, 2006 for a review and meta-analysis). Furthermore, neuropsychological studies have reported better cognitive test performance (Plassman et al, 1995;Wilson et al, 2009) and reduced rate of cognitive decline (Albert et al, 1995;Alvarado et al, 2002;Anstey et al, 2003;Christensen et al, 1997;Evans et al, 1993;Farmer et al, 1995;Lyketsos et al, 1999;White et al, 1994) in elders with higher levels of education.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Valenzuela and Sachdev (2006a) assessed the evidence on the relation between mental activity and dementia and reported that "six large longitudinal studies have now found that increased levels of leisure and mental activity in late life are associated with an approximate 50% lower incidence of dementia" (p. 450). In a further article, the same authors conducted a meta-analysis involving over 47,000 individuals and concluded that higher levels of brain reserve were related to decreased rates of cognitive decline in old age (Valenzuela & Sachdev, 2006b). These conclusions are not universally accepted, however; for example, Salthouse (2006) has pointed out that individuals with better functioning brains may be the ones to participate more fully in stimulating activities.…”
mentioning
confidence: 99%
“…Age is also a very strong independent predictor for leukoaraiosis. Education affects performance on some cognitive tests, as people with higher educational attainment tend to perform better (Valenzuela & Sachdev, 2006). For this analysis, education was categorized as follows: 0) less than high school, 1) completed high school (GED), 2) some college, and 3) completed college (4+ years).…”
Section: Covariatesmentioning
confidence: 99%